Sexual dysfunction in women with rheumatic diseases - O. V. Teplyakova; A. A. Morozova; A. A. Popov (Современная ревматология)
Objective: to assess sexual function in female patients with rheumatoid arthritis (RA) and fibromyalgia (FM) and to identify the main risk factors of sexual dysfunction (SD).Patients and methods. 60 patients with FM (mean age 44.2±10.1 years) – Group 1; 69 patients with RA (mean age 45.0±9.6 years) – Group 2; and 100 healthy women controls (mean age 45.1±11.8 years) – Group 3 were enrolled in the study. Medical history, severity of pain at rest and during movement by visual analog scale (VAS), and anxiety and depression symptoms by hospital anxiety and depression scale (HADS) were assessed. Sexual function was evaluated by «Female Sexual Function index (FSFI)».Results and discussion. The overall sexual function score in Group 1 (12.7±9.0) was almost twice lower than in the control group (23.55±8.24, p<0.001) and in Group 2 (20.9±11, p<0.001). There was no difference between RA patients group and control group, where the average score for each of the scales was above 3 (with the exception of the «desire» scale). In FM patients all scales were below 3 points, which indicated significant SD, score on the «orgasm» scale was the lowest (1.8±0.9), and score on «absence of sexual pain» scale was the highest (2.6±1.8). SD in patients with FM was significantly driven by affective disorders presenting with anxiety and depression. Inflammatory activity and severity of pain by VAS were strongly associated with SD in RA group. The divorced person status was associated with the development of SD, regardless of nosological diagnosis.Conclusion. RA and FM have a negative impact on women's sexual function. The inflammatory disease activity is the main driver of SD in RA patients while affective disorders promote SD in FM patients.